Intervention in Parents to Prevent Sexual Abuse in Children: Literature Review - Tetti Solehati; Sri Mayang Rahayu; Hilmi Adillah; Dian Triyani; Gihon Jessi Novita; Aisha Chaerani Murti; Yanti Hermayanti; Cecep Eli Kosasih; Henny Suzana Mediana (LPPM STIKES KENDAL, 2021)
Child Sexual Abuse is a fairly broad global problem. One of the contributing factors is the negligence of the parents in paying attention to the safety of the child which makes the child a victim of Child Sexual Abuse. Intervention is needed for parents in the prevention of CSA. The research objective to explore effective interventions for parents in preventing child sexual abuse. Literature search using the National Library of Indonesia database in English and Indonesian, published between 2010 and 2020, CINAHL, Science Direct, PubMed, and ProQuest with full text inclusion requirements, primary research, quasi-experimental research design, and RCT. After searching, it found 42 articles that met the incorporation and brought about in 3 articles that met the requirements after assessing the articles using JBI. Results: It was found that interventions in parents using counselling, education using video, school education, and psychoeducation were effective in increasing self-efficacy, knowledge, behaviors, and undestanding of the prevention of obesity. Various forms of intervention in the parents are effective in Child Sexual Abuse Prevention.